Balancing Roles and Responsibilities: A Study on Challenges and Strategies of Female English Teachers: Balancing Roles and Responsibilities: A Study on Challenges and Strategies of Female English Teachers - Ayu Linda Oktavia; Durratul Hikmah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the challenges and strategies of female English teachers in East Java, Indonesia, in balancing professional and personal roles within a patriarchal cultural context. Using a phenomenological approach, the research identifies five main challenges: time management difficulties, domestic and family role challenges, psychological burdens, gender-related social pressure, and environmental issues. To address these, teachers employ coping strategies within Lazarus and Folkman’s framework, including problem-focused coping (time management, prioritization, seeking support) and emotion-focused coping (emotional support, mindfulness, relaxation, and positive reframing). Findings highlight female teachers’ resilience and proactive efforts in navigating dual roles. The study offers insights for educators, institutions, and policymakers to create more supportive, gender-sensitive environments.